(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article Timurid queens life , work , rich and cool creative - scientific heritage , of queens not only in the family a child upbringing rather , the state in management too his own instead of have that it was historical sources based on reflection to continue and this edges student to the girls to teach the garden is cultivated . In the article from this except from the audience except training through of students spirituality development important factors , they between healthy spiritual environment content in finding ancestors spiritual and moral inheritance deep learning about thought held .